MANAGEMENT OF CHRONIC KIDNEY DISEASE IN AYURVEDIC SETTING : A CASE REPORT - Yadav Ritu; J.P. Singh; Sahu Ajay Kumar; Sharma Pankaj (International Journal of Applied Ayurved Research, 2017)
Chronic diseases have become a major public health problem. Chronic diseases are a leading cause of morbidity and mortality in India and other low and middle income countries. The chronic diseases account for 60% of all deaths worldwide. Here we are reporting a case of CKD of a 34 year old male patient. The direct description of the disease is not available in Ayurvedic science, So we can compare the disease with Ayurvedic concepts only on the basis of general signs and symptoms. The possible understanding of the case in terms of Ayurveda and a therapeutic protocol with promising result has been discussed.Clinical finding of the patients suggest that chronic kidney disease is a disease of Mutravaha Strotas. So our aim was to improve the function of Mutravaha Srotas by Mutravaha Srotosudhi.The initial clinical history of the patient suggest that there agnimandyata and amadoshasanchaya play a important role in Mutravaha srotodusti.So aamdoshapachan along with mutravaha srotosodhan formed the basics of our treatment protocol.Our treatment protocol shows significant results in reduction blood urea and Serum creatinine level. Aalong with objective parameters significant results was obtained in subjective finding like marked reduction in swelling in bilateral lower limb,generalizrd weakness,pain in lower back etc in significant interval of time.